Scaffolding in second language teaching. The teaching unit “The poem ‘Der Herbst steht auf der Leiter’ by Peter Hacks“ - Schulz-Andrzejewska, Joanna (Scripta Neophilologica Posnaniensia, 2020)
This article presents a lesson plan for German taught as a second language in Middle School. The plan shows the creative integration of a poem by Peter Hacks into the lesson. The artful and partly three-dimensional work improves the understanding of the text and benefits the student’s feeling for the language. The students are guided to the underlying objective through different tasks. In the end, they memorize the poem and present it in front of the class.